2011
DOI: 10.1007/s11302-011-9253-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological level of norepinephrine increases adenine nucleotides hydrolysis in rat blood serum

Abstract: Extracellular adenosine 5'-triphosphate (ATP) and its breakdown products, adenosine 5'-diphosphate (ADP) and adenosine, have significant effects on a variety of biological processes. NTPDase enzymes, responsible for adenine nucleotides hydrolysis, are considered the major regulators of purinergic signaling in the blood. Previous work by our group demonstrated that ATP and ADP hydrolysis in rat blood serum are higher during the dark (activity) phase compared to the light (rest) phase. In nocturnal animals (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Nonetheless, although be- yond the current scope of our work, to further evaluate the pro-osteogenic of MLT in aged female rodents will help to fully reveal the mechanisms underlying MLT's effects. The dosage of exogenous MLT used in this study is 30 mg/kg, which is much higher than its physiological dose [23]. Therefore, we believe that the administration time of exogenous MLT does not affect its effects.…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, although be- yond the current scope of our work, to further evaluate the pro-osteogenic of MLT in aged female rodents will help to fully reveal the mechanisms underlying MLT's effects. The dosage of exogenous MLT used in this study is 30 mg/kg, which is much higher than its physiological dose [23]. Therefore, we believe that the administration time of exogenous MLT does not affect its effects.…”
Section: Discussionmentioning
confidence: 91%
“… 55 In a previous study, we demonstrated that norepinephrine increases soluble NTPDase 1-like activity in blood serum through a direct stimulatory effect. 20 This positive modulatory effect suggests a new role for circulating norepinephrine in regulation of nucleotidases (likely soluble NTPDase-1) pathway, where it may induce a decrease in extracellular ATP and ADP in the circulation. 20 Taking into account that morphine treatment in early life changes soluble nucleotidase activities in rat serum over the medium- and long-term, observed increased NTPDase 1-like and 5′-nucleotidase at P30, and decreased NTPDase 1-like at P60, we can suggest that, at these different ages, soluble nucleotidases modulate the cardiovascular tonus by controlling nucleotide levels in the blood serum, such as increased adenosine levels at P30 and increased ADP levels at P60.…”
Section: Discussionmentioning
confidence: 99%
“… 20 This positive modulatory effect suggests a new role for circulating norepinephrine in regulation of nucleotidases (likely soluble NTPDase-1) pathway, where it may induce a decrease in extracellular ATP and ADP in the circulation. 20 Taking into account that morphine treatment in early life changes soluble nucleotidase activities in rat serum over the medium- and long-term, observed increased NTPDase 1-like and 5′-nucleotidase at P30, and decreased NTPDase 1-like at P60, we can suggest that, at these different ages, soluble nucleotidases modulate the cardiovascular tonus by controlling nucleotide levels in the blood serum, such as increased adenosine levels at P30 and increased ADP levels at P60. Although adenosine is well-known to inhibit platelet aggregation and ADP induces platelet aggregation and vasoconstriction, we do not know whether nucleotides exert the mentioned functions in the medium- and long-term after morphine treatment in early life, as several other factors, are very important in determining the direction of the vascular response elicited by adenine nucleotides, such as the presence and nature of the purinoceptor subtype involved and its location in relation to the structural components of the vascular wall.…”
Section: Discussionmentioning
confidence: 99%